(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Aim: The low bone mass as presented as osteopenia and osteoporosis represent example of the morbidities that occur in patients with chronic obstructive pulmonary disease (COPD). Predictors of bone mass density include osteopenia and osteoporosis. There is little data from Iraq on the relation between COPD and low bone mass. This study aimed to assess predictors of bone mass density in COPD patients attending Merjan Medical City. Patients and Methods: The study was performed on patients with COPD patients seen at the Merjan Medical City in the period between January 2018 and June 2019. The study included taking history with physical examination in addition to the needed investigation which included spirometry and dual-energy X-ray absorptiometry (DEXA) scan, osteopenia was defined if the T score was -<1 to <-2.5 and osteoporosis of <-2.5 as according to the WHO guidelines. Results: The study involved 122 patients with COPD, average age was 61.52±10.01, males were 107 (88.52%) and females were 15 (11.48%), 22 patients (18.03%) had normal bone mass while the remaining 100 (81.97%) had with low bone mass, 64 (52.46%) were osteoporotic and 36 patients (29.51%) had osteopenia. There was also significant relation between T score and FEV1, (P value= 0.000), significant relation between T score and smoking (P value 0.000), in addition there was significant relation between pack year and severity of airways obstruction as assessed by pulmonary function test (P value 0.000). Conclusions: Our study shows that patients with low bone mass that presented as osteopenia and osteoporosis form high percentage in patients with COPD and greatly related to disease severity and amount of smoking.